Perseverance in gratitude a socio-rhetorical commentary on the Epistle "to the Hebrews" - deSilva, David Arthur (Grand Rapids, MI Eerdmans, 2000)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Hebrews -- socio-rhetorical criticism